PENGEMBANGAN PRODUK MI KERING DARI TEPUNG UBI JALAR (Ipomoea batatas) DAN PENENTUAN UMUR SIMPANNYA DENGAN METODE ISOTERM SORPSI [Development of Dried Noodle Made of Sweet Potato (Ipomoea batatas) Flour and Prediction of Its Shelf Life Using Sorption Isoth - . Sugiyono; Edi Setiawan; Elvira Syamsir; Hery Sumekar (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
The objective of this research was to develop dried noodle product made of sweet potato flour and to predict its shelf life using sorption isotherm method. The product was produced through gelatinization of dough, followed by sheeting, steaming, and drying. The best quality product was produced through gelatinization for 20 minutes followed by steaming for 10 minutes. The best quality product had 5.86% moisture, 3.10% ash, 0.23% fat, 2.66% protein, and 88.15% carbohydrate. The product had 54.43 degree of whiteness, 28.75 gf of elasticity, 3.5 minutes of rehydration time, 53.23% of water absorption capacity, and 14.85% of cooking loss. The sorption isotherm curve of the product was best described by Henderson model. The shelf lives of the packed product in low density polyethylene, medium density polyethylene, high density polyethylene, and polypropylene at 80% RH were calculated to be 55, 92, 277 and 150 days respectively.